Optimizing the distribution pattern of species under climate change: the protection and management of Phellodendron amurense in China - Zhang, Boyan; Zou, Hui; Chen, Bingrui; Zhang, Xiyuan; Kang, Xun; Wang, Chen; Zhang, Xinxin (Frontiers in Ecology and Evolution, 2023)
Objective Phellodendron amurense, a special species in Northeast Asia, is the source of the wild medicinal Phellodendri Amurensis Cortex, the second-level key protection in China. Because of its dual value of medicine and timber, it has been cut in large quantities, resulting in a sharp decline in wild resources. It has been listed as a national first-class rare tree species. Here, we aim to plan protection area and wild tending area for Chinese P. amurense in the context of climate change. Method In this study, based on the Biomod2 model, the main environmental factors affecting the distribution and the potentially suitable areas of the current and future were investigated. Furthermore, the correlation between the main environmental factors and the chemical components was determined by full subset regression. Habitat quality and landscape pattern change were determined by InVEST and Fragstats software based on the land use data in 1980, 2000, and 2020. Then, Zonation software was used to plan the priority protection and wild tending areas. Results The results showed that in the future, the potential habitat of P. amurense will gradually move to the high latitude and high altitude areas in the northwest direction, and the high suitability area will decrease sharply. Since 1980, the habitat quality of P. amurense habitat has gradually deteriorated, and the fragmentation has gradually intensified. In the future, the central part of the Greater Khingan Mountains and the forest area of the Lesser Khingan Mountains will be the long-term stable sanctuary. Fengcheng City and Tonghua County are the most suitable for the wild tending areas. Conclusion The existing nature reserve only contains 6.01% of the priority protection area, so we propose to expand the area to cover a larger proportion of the sanctuary and implement management and restoration plans to increase the suitability and connectivity. These results can support the protection action and provide a reference and scientific basis for further research, rational development, and utilization of P. amurense.